Air-grade zircon powder gradient calcination halogenation impurity removal and multi-stage magnetic separation purification process
Patent Information
- Application Number
- CN202611214969.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于提供航空级锆英粉梯度煅烧卤化除杂与多级磁选纯化工艺,解决了针对天然锆英砂中赋存状态、热响应和磁响应不同的伴生杂质缺乏连续纯化工艺,以及制粉过程中铁质杂质易重新引入的技术问题
本发明通过建立从原料预处理到粒度调控的连续工艺链,解决了天然锆英砂中赋存状态和磁响应各异的伴生杂质难以系统性去除的技术问题。该连续工艺链将低添加量复配卤化体系下的梯度煅烧、递进式三级电磁分选和锆质接触制粉依序衔接,使得能够通过热作用发生状态变化的杂质在先接受连续热历程处理,残留且具有不同磁响应强度的杂质再按磁场强度由低至高的顺序逐级分离,完成去铁后再以锆质材料作为直接接触研磨表面,从工艺顺序上减少制粉阶段铁质磨损物的重新引入。由此,不同性质和赋存状态的伴生杂质分别在煅烧、磁选和制粉环节得到针对性处理,各工序之间形成输入输出约束关系,避免了传统流程中将焙烧、磁选和磨粉分别独立设置时所导致的前一工序处理效果在后一工序中被抵消或弱化的问题,综合提升了杂质去除效果并提高了锆英粉的耐火度。
Smart Images

Figure CN122977837A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of special refractory ceramic raw material processing technology, specifically to a gradient calcination halogenation purification and multi-stage magnetic separation purification process for aerospace-grade zircon powder. Background Technology
[0002] Zircon sand's main mineral, zircon, possesses high refractory temperature and high-temperature chemical stability, making it suitable as a raw material for precision casting core refractory powder. Natural zircon sand, influenced by deposit composition and associated minerals, may contain iron-, titanium-, aluminum-, manganese-, and nickel-containing minerals, as well as surface deposits, in addition to zircon. Some impurities exist as independent particles, while others adhere to, intergrow with, or encapsulate zircon, and different impurities exhibit varying thermal and magnetic responses. Single magnetic separation is insufficient to simultaneously address impurities with different magnetic responses, and single high-temperature treatment is also insufficient to establish a phased effect for different occurrence states. Halogen-containing systems can participate in the state regulation of some associated impurities under heating conditions, but excessive fluorine-containing systems may deviate from the treatment objective of producing zircon sand refractory powder; therefore, it is necessary to control the amount of halogen-containing components and the thermal process. Magnetic response impurities remaining after gradient calcination require further separation.
[0003] On the other hand, if zircon sand after iron removal is ground using iron liners or steel abrasive media, the abrasive material may reintroduce iron impurities. For zircon powder requiring further surface functionalization, the mass transfer conditions during gas penetration through the bed also affect the formation of the surface pore structure. Existing processes typically separate calcination, magnetic separation, and grinding, lacking continuous constraints between the output state of the previous process and the separated object in the next process, and also lacking clear control over the penetration state of the inert carrier gas in the high-temperature bed and its relationship with the surface pore structure. If the resulting zircon powder is to not only meet the requirements for refractory powder use but also possess adsorption carrier functions, it is necessary to confirm the formed surface structure and its performance through measurable pore structure parameters and adsorption kinetic data. Summary of the Invention
[0004] The purpose of this invention is to provide a gradient calcination halogenation impurity removal and multi-stage magnetic separation purification process for aerospace-grade zircon powder, which solves the technical problems of lack of continuous purification process for associated impurities with different occurrence states, thermal responses and magnetic responses in natural zircon sand, and the easy reintroduction of iron impurities during the powdering process.
[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: The gradient calcination, halogenation, and multi-stage magnetic separation purification process for aerospace-grade zircon powder includes the following steps: S1. Raw material pretreatment: The natural zircon sand ore is screened and dusted to remove large foreign objects, lumps and free dust to obtain zircon sand raw material; S2. Compound halogenation gradient calcination: Zircon sand raw material is mixed with a compound halogenating agent composed of ammonium fluoride and ammonium chloride. The mass ratio of ammonium fluoride to ammonium chloride is 1:1.20-1.35, and the total amount of compound halogenating agent added is 1.5%-2.0% of the mass of zircon sand raw material. The mixed material is placed under an inert atmosphere, and the same batch of material is subjected to a first stage calcination at 500℃, a second stage calcination at 800℃, and a third stage calcination at 1200℃ without leaving the furnace. The holding time for the first stage calcination at 500℃ is 30-45 min, the holding time for the second stage calcination at 800℃ is 40-50 min, and the holding time for the third stage calcination at 1200℃ is 90-100 min. The heating rate between each stage is 5-6℃ / min. S3. Cooling treatment: After the third stage of calcination at 1200℃ is completed, heating is stopped, and the calcined material is cooled to room temperature with the furnace. Agglomerates that affect the subsequent stable supply are deagglomerated to obtain high-temperature purified zircon sand semi-finished product. S4. Progressive three-stage electromagnetic separation: The main stream of high-temperature purified zircon sand semi-finished product first passes through the first stage electromagnetic separation with a magnetic field strength of 0.8T. The main zircon sand stream obtained from the first stage electromagnetic separation is then sent to the second stage electromagnetic separation with a magnetic field strength of 1.0T. Finally, the main zircon sand stream obtained from the second stage electromagnetic separation is sent to the third stage electromagnetic separation with a magnetic field strength of 1.2T to obtain magnetically separated zircon sand concentrate. S5. Zirconium Contact Grinding: After the third-stage electromagnetic separation is completed, the magnetically separated zircon sand concentrate is ground. The grinding equipment liner and grinding media that are in direct contact with the magnetically separated zircon sand concentrate are made of zirconium material. The zirconium material is a zirconium-containing non-ferrous material that forms the direct contact surface, and ferrous materials are not used as the main grinding material in direct contact with the magnetically separated zircon sand concentrate. S6. Particle size control: The powder obtained from grinding is sieved and classified to obtain aerospace-grade zircon powder.
[0006] As a preferred embodiment of the present invention, the total amount of compound halogenating agent and the mass ratio of ammonium fluoride to ammonium chloride are selected from one of the following combinations: the total amount of compound halogenating agent is 1.5% of the mass of zircon sand raw material, and the mass ratio of ammonium fluoride to ammonium chloride is 1:1.20; or the total amount of compound halogenating agent is 2.0% of the mass of zircon sand raw material, and the mass ratio of ammonium fluoride to ammonium chloride is 1:1.35.
[0007] As a preferred embodiment of the present invention, the gradient calcination parameters are selected from one of the following combinations: the heating rate between each stage is 5℃ / min, the first stage calcination is held at 500℃ for 30min, the second stage calcination is held at 800℃ for 40min, and the third stage calcination is held at 1200℃ for 90min; or the heating rate between each stage is 6℃ / min, the first stage calcination is held at 500℃ for 45min, the second stage calcination is held at 800℃ for 50min, and the third stage calcination is held at 1200℃ for 100min.
[0008] As a preferred technical solution of the present invention, the total amount of compound halogenating agent added is 2.0% of the mass of zircon sand raw material, the mass ratio of ammonium fluoride to ammonium chloride is 1:1.35, the heating rate between each stage is 6℃ / min, the first stage calcination is held at 500℃ for 45min, the second stage calcination is held at 800℃ for 50min, and the third stage calcination is held at 1200℃ for 100min.
[0009] As a preferred embodiment of the present invention, the total amount of compound halogenating agent added is 1.5% of the mass of zircon sand raw material, the mass ratio of ammonium fluoride to ammonium chloride is 1:1.20, the heating rate between each stage is 5℃ / min, the first stage calcination is held at 500℃ for 30min, the second stage calcination is held at 800℃ for 40min, and the third stage calcination is held at 1200℃ for 90min.
[0010] As a preferred embodiment of the present invention, the first, second and third stages of electromagnetic separation are carried out continuously in the order of increasing magnetic field strength of 0.8T, 1.0T and 1.2T. The main zircon sand stream obtained from the first stage of electromagnetic separation is used as the feed for the second stage of electromagnetic separation, and the main zircon sand stream obtained from the second stage of electromagnetic separation is used as the feed for the third stage of electromagnetic separation.
[0011] As a preferred technical solution of the present invention, the zirconium contact powdering is located after the three-stage electromagnetic separation. In the grinding equipment, the liner and grinding media that are in direct and continuous contact with the magnetically separated zirconium sand concentrate are both made of zirconium material to form a direct contact surface.
[0012] As a preferred embodiment of the present invention, the particle size distribution formed in step S6, based on the total mass of three qualified particle grades—100-200 mesh, 200-320 mesh, and powder passing through a 320 mesh sieve—is as follows: 40%-50% of the 100-200 mesh particles passing through a 100 mesh sieve and retained by a 200 mesh sieve; 30%-40% of the 200-320 mesh particles passing through a 200 mesh sieve and retained by a 320 mesh sieve; and 10%-20% of the powder passing through a 320 mesh sieve; and the sum of the mass percentages of the three qualified particle grades is 100%.
[0013] As a preferred embodiment of the present invention, 45% of the particles are of 100-200 mesh, 35% are of 200-320 mesh, and 20% are powder passing through a 320 mesh sieve.
[0014] As a preferred embodiment of the present invention, 50% of the particles are of 100-200 mesh, 30% are of 200-320 mesh, and 20% are powder passing through a 320 mesh sieve.
[0015] As a preferred embodiment of the present invention, during the third-stage calcination at 1200℃ in step S2, argon gas is used as an inert carrier gas, allowing the argon gas to pass through the material bed from below, and the linear velocity between the pores in the material bed is controlled according to the following formula:
[0016] In the formula: This represents the linear velocity of argon gas in the pores of the material bed, expressed in m / s. This represents the actual volumetric flow rate of argon gas after correction for the working temperature and pressure of the gradient calcination equipment, in m³ / s. The porosity of the material bed is expressed as a dimensionless decimal. This represents the effective cross-sectional area of the material bed region in the gradient calcination equipment, expressed in m²; where the linear velocity between the pores in the bed is measured during the third stage of calcination at 1200℃. The setting value is 0.030 m / s to adjust the mass transfer contact conditions between the halogen-containing gas phase component formed during the continuous heating process and the surface of the zircon sand particles, so that the obtained aerospace-grade zircon powder forms a mesoporous structure.
[0017] The aerospace-grade zircon powder with a mesoporous structure prepared by the above process was applied to the adsorption and removal of Pb(II), Cd(II), and Cr(VI) species in an aqueous system. The adsorption kinetic data of Pb(II), Cd(II), and Cr(VI) species were fitted using the following pseudo-second-order kinetic model integral expression:
[0018] In the formula: This indicates the adsorption contact time, in minutes. The adsorption contact time is indicated as The instantaneous adsorption capacity of a unit mass of aerospace-grade zircon powder for the corresponding target species, expressed in mg / g; The equilibrium adsorption capacity obtained by fitting the pseudo-second-order kinetic model is expressed in mg / g. The coefficient of determination represents the pseudo-second-order adsorption rate constant, expressed in g / (mg·min); when performing linear fitting on data obtained under the same adsorption test conditions, the coefficients of determination for the Pb(II), Cd(II), and Cr(VI) species are given. All are no less than 0.997.
[0019] Compared with the prior art, the present invention has the following beneficial effects: This invention solves the technical problem of systematically removing associated impurities with varying occurrence states and magnetic responses in natural zircon sand by establishing a continuous process chain from raw material pretreatment to particle size control. This continuous process chain sequentially connects gradient calcination in a low-addition compound halogenation system, progressive three-stage electromagnetic separation, and zirconium contact grinding. This allows impurities capable of undergoing state changes through thermal action to undergo continuous thermal treatment first, while residual impurities with different magnetic response intensities are then separated step-by-step according to increasing magnetic field strength. After iron removal, zirconium material is used as the direct contact grinding surface, reducing the reintroduction of ferrous abrasives during the grinding stage. Thus, associated impurities with different properties and occurrence states are specifically treated in the calcination, magnetic separation, and grinding stages, forming an input-output constraint relationship between each process. This avoids the problem in traditional processes where calcination, magnetic separation, and grinding are set up independently, leading to the cancellation or weakening of the treatment effect of the previous process in the subsequent process. This comprehensively improves the impurity removal effect and enhances the refractoriness of the zircon powder.
[0020] Furthermore, during the third-stage calcination at 1200℃, the flow state of argon gas through the material bed is quantitatively controlled by the linear velocity between the pores in the bed. This allows the mass transfer contact conditions between the halogen-containing gas phase components and the surface of the zircon sand particles to be precisely correlated through gas flow rate, bed porosity, and effective cross-sectional area. The resulting zircon powder forms a pore structure dominated by mesopores, which significantly increases the specific surface area and pore volume. This endows the zircon powder with the adsorption function of lead, cadmium, and hexavalent chromium species in the aqueous phase, expanding the application range of aerospace-grade zircon powder. Attached Figure Description
[0021] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.
[0022] Figure 1 This is the main process flow diagram of the present invention. Detailed Implementation
[0023] In the following description, only certain exemplary embodiments are briefly described. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of the embodiments of the invention. Therefore, the drawings and description are considered to be exemplary in nature and not restrictive.
[0024] The following is in conjunction with the appendix Figure 1 The embodiments of the present invention will be described in detail below.
[0025] In this invention, natural zircon sand uses raw materials with clearly identified batch numbers. When comparing the examples with the control, natural zircon sand from the same source batch is used. The amount of halogenating agent added is calculated based on the actual mass of the zircon sand raw material entering the gradient calcination step after screening and dust removal. Ammonium fluoride and ammonium chloride use raw materials with clearly identified batch numbers and purity levels and are measured separately. Let the mass of the zircon sand raw material entering the gradient calcination step be... The unit is kg; the total mass fraction of the compound halogenating agent added is The mass ratio of ammonium chloride to ammonium fluoride is expressed as a dimensionless decimal. ,Right now:
[0026] In the formula: This indicates the mass of ammonium chloride, expressed in kg. This indicates the mass of ammonium fluoride, expressed in kg. The mass of zircon sand raw material entering the gradient calcination step is expressed in kg. The total mass fraction of compound halogenating agents added is expressed as a dimensionless decimal. This indicates the mass ratio of ammonium chloride to ammonium fluoride. The mass of ammonium fluoride fed is calculated using the following formula:
[0027] In the formula: This indicates the mass of ammonium fluoride, expressed in kg. The mass of zircon sand raw material entering the gradient calcination step is expressed in kg. The total mass fraction of compound halogenating agents added is expressed as a dimensionless decimal. This indicates the mass ratio of ammonium chloride to ammonium fluoride. The mass of ammonium chloride fed is calculated using the following formula:
[0028] In the formula: This indicates the mass of ammonium chloride, expressed in kg. The mass of zircon sand raw material entering the gradient calcination step is expressed in kg. The total mass fraction of compound halogenating agents added is expressed as a dimensionless decimal. This indicates the mass ratio of ammonium chloride to ammonium fluoride. The masses of the two halogenating agents satisfy:
[0029] In the formula: This indicates the mass of ammonium fluoride, expressed in kg. This indicates the mass of ammonium chloride, expressed in kg. The mass of zircon sand raw material entering the gradient calcination step is expressed in kg. This indicates the total mass fraction of the compounded halogenating agent, expressed as a dimensionless decimal. When kg, , At that time, the mass of ammonium fluoride was approximately 0.851 kg, and the mass of ammonium chloride was approximately 1.149 kg, totaling 2.000 kg; when kg, , At that time, the mass of ammonium fluoride was approximately 0.682 kg, the mass of ammonium chloride was approximately 0.818 kg, and the total mass of the two was 1.500 kg.
[0030] During raw material pretreatment, the natural zircon sand ore is screened to remove large minerals, lumps, and foreign matter that are significantly larger than the main zircon sand particle size. Then, dust removal is performed to remove free dust and free fine powder that may affect the quality benchmark of subsequent batching. The zircon sand after screening and dust removal is used as the quality benchmark for compound halogenating agent.
[0031] The compound halogenating agent consists of ammonium fluoride and ammonium chloride. Ammonium fluoride and ammonium chloride undergo thermal behavior changes during continuous heating. The "halogenation impurity removal" or "halogen-containing reaction environment" referred to in this specification includes the initial addition of ammonium fluoride and ammonium chloride, as well as the process of halogen-containing components formed by the compound halogenation system during continuous heating, participating in the regulation of associated impurities. After determining the net feed mass of the zircon sand raw material, the total mass of the compound halogenating agent is calculated according to the total added mass fraction. Then, the masses of the two halogenating agents are allocated according to the mass ratio of ammonium fluoride to ammonium chloride, measured separately, mixed with the zircon sand raw material, and fed into the gradient calcination equipment.
[0032] During the first stage of calcination at 500℃, the mixture is fed into a gradient calcination device and an inert atmosphere is established. The temperature is increased to 500℃ at a rate of 5–6℃ / min and held for 30–45 minutes. This allows the adsorbed components, easily desorbed components, and some thermally unstable associated components in the raw materials to undergo thermal state changes first, and enables the compound halogenation system to enter a continuous heating process. The material is not discharged from the furnace after the first stage at 500℃.
[0033] During the second stage of calcination at 800℃, the temperature is further increased to 800℃ and held for 40–50 minutes. The material, which has undergone the first stage treatment at 500℃, continues to be heated, and the surface state, thermal state, and contact state with the halogen-containing environment of the associated impurities continue to change. The material is not removed from the furnace after the second stage at 800℃.
[0034] During the third stage of calcination at 1200℃, the temperature is further increased to 1200℃ and held for 90–100 minutes. The zircon sand entering the third stage at 1200℃ has already undergone two stages at 500℃ and 800℃, which are used to further activate, migrate, or adjust the state of residual and associated impurities from the first two stages. The three stages are carried out sequentially by the same batch of main material, without cooling the material and re-feeding it into the furnace between stages, and are continuously transitioned according to the set heating rate.
[0035] In a further embodiment, the gradient calcination equipment is equipped with a gas distribution structure located below the material bed, allowing argon gas to enter from below the material bed and pass through the pores between the material particles along the thickness direction of the material bed. The argon gas purity is 99.999%. After the equipment is sealed, residual air is first evacuated, and then argon gas is introduced to replace it and establish an inert atmosphere. When the material reaches 1200°C and enters the third stage of the heat preservation process, argon gas is continuously passed through the material bed, and the linear velocity between the pores of the bed is maintained. Determine using the following formula:
[0036] In the formula: This represents the linear velocity of argon gas in the pores of the material bed, expressed in m / s. This represents the actual volumetric flow rate of argon gas after correction for the working temperature and pressure of the gradient calcination equipment, in m³ / s. The porosity of the material bed is expressed as a dimensionless decimal. This represents the effective cross-sectional area of the material bed in the gradient calcination equipment, expressed in m². The argon gas flow rate entering the equipment is controlled by a mass flow control system. The flow rate reading is corrected for operating temperature and pressure to obtain the actual volumetric flow rate used for calculation. In Example 3, the linear velocity between the pores of the bed was set to 0.030 m / s. Under this flow condition, argon gas continuously passed through the material bed to regulate the convective transport, diffusion, and mass transfer contact state of the halogen-containing gas phase components in the particle bed with the particle surface.
[0037] After the third stage of calcination at 1200℃ is completed, heating is stopped, and the calcined material is left in the gradient calcination equipment to cool to room temperature in the furnace. The material after cooling in the furnace is checked for its condition, and any agglomerates that affect the subsequent stable entry into the electromagnetic separation equipment are mechanically deagglomerated to restore the material to a particle state that can stably enter the separation area, thus obtaining the high-temperature purified zircon sand semi-finished product.
[0038] In the progressive three-stage electromagnetic separation process, the high-temperature purified zircon sand semi-finished product is fed into the first-stage electromagnetic separation zone with a magnetic field strength of 0.8T, preferentially separating impurities that form usable magnetic response differences under the 0.8T magnetic field condition. The main zircon sand stream obtained from the first stage enters the second-stage electromagnetic separation zone with a magnetic field strength of 1.0T. The main zircon sand stream obtained from the second stage enters the third-stage electromagnetic separation zone with a magnetic field strength of 1.2T. After the three-stage electromagnetic separation is completed, magnetically separated zircon sand concentrate is obtained. The three-stage separation maintains the main stream sequence of 0.8T→1.0T→1.2T, and the electromagnetic separation feed rate is calibrated according to the equipment's historical calibration conditions.
[0039] The process connection between gradient calcination and three-stage electromagnetic separation is as follows: gradient calcination is performed before three-stage electromagnetic separation. Associated components in natural zircon sand that can undergo desorption, decomposition, or state adjustment through continuous heating are first subjected to gradient calcination. Mineral particles that remain after gradient calcination and cooling and have usable differences in magnetic response then enter the three-stage electromagnetic separation.
[0040] After completing the 1.2T third-stage electromagnetic separation, magnetically separated zircon sand concentrate is obtained and then enters the grinding equipment. The grinding equipment liners and grinding media that directly contact the magnetically separated zircon sand concentrate are made of zirconium-based material. This zirconium-based material is a non-ferrous, zirconium-containing material that forms the direct contact surface; ferrous materials are not used as the main grinding material in direct contact with the magnetically separated zircon sand concentrate. Zirconium-based contact grinding is set after the third-stage electromagnetic separation, which already removes iron-containing impurities associated with the magnetic response. Therefore, the grinding stage avoids using a ferrous main material in direct contact with the grinding material. During production, initial operating parameters are set according to the historical calibration conditions of the grinding equipment, and the grinding endpoint is determined by the results of 100-mesh, 200-mesh, and 320-mesh sieve tests.
[0041] The zircon powder obtained from grinding was dry-sieved sequentially using 100-mesh, 200-mesh, and 320-mesh sieves. Powder passing through the 100-mesh sieve but retained by the 200-mesh sieve was defined as the 100–200 mesh particle size; powder passing through the 200-mesh sieve but retained by the 320-mesh sieve was defined as the 200–320 mesh particle size; and powder passing through the 320-mesh sieve was defined as the powder that passed through the 320-mesh sieve. Excessively coarse powder passing through the 100-mesh sieve was not included in the mass composition statistics of the three qualified particle sizes. The three qualified particle sizes were weighed separately and normalized to a total mass of 100–200 mesh, 200–320 mesh, and the powder passing through the 320-mesh sieve, which was set as 100%. Let the mass percentage of the 100–200 mesh particle size be... The mass percentage of particles in the 200-320 mesh range is The percentage of powder by mass passing through a 320-mesh sieve is ,but:
[0042] In the formula: This indicates the percentage of the total mass of the three qualified particle sizes in the 100-200 mesh range. This indicates the percentage of the total mass of the three qualified particle sizes in the 200-320 mesh range. This indicates the percentage by mass of powder passing through a 320-mesh sieve, representing the total mass of the three acceptable particle sizes. Preferably, it meets the following requirements. , , and simultaneously satisfy .
[0043] For impurity evaluation, the same elemental analysis methods, sample pretreatment methods, statistical items, instrument calibration systems, and mass fraction statistical standards were used to compare impurities in Examples 1, 2, and Comparative Example 1. The reduction rate of total impurity content was also considered. Calculate according to the following formula:
[0044] In the formula: This indicates the rate of reduction in total impurity content, expressed in % . This represents the total mass fraction of impurities obtained in Comparative Example 1 using the same elemental analysis method and the same statistical items. The total mass fraction of impurities in the examples is indicated by the same conditions as Comparative Example 1. The refractoriness was evaluated using the same sample preparation method, the same equipment, and the same heating and judgment procedures. The zircon powders obtained in Examples 1 and 2 have a refractoriness of over 1850°C, while the zircon powder obtained in Comparative Example 1 has a refractoriness of 1720°C.
[0045] For mesoporous structure evaluation, zircon powder samples were placed in the sample tube of a surface area and porosity analyzer. Degassing was performed at 300℃ for 240 min, followed by nitrogen adsorption and desorption tests under liquid nitrogen conditions. Specific surface area was calculated using the BET method, pore size distribution using the BJH method, and total pore volume was obtained using the same instrument and data processing procedures. Mesoporous volume fraction was defined. The pore volume corresponding to the pore size range of 2–50 nm Percentage of total pore volume obtained from testing Percentage:
[0046] In the formula: This represents the mesoporous volume fraction, expressed in % %. This represents the cumulative pore volume corresponding to a pore size range of 2–50 nm, expressed in cm³ / g. This represents the total pore volume obtained under the same test conditions, expressed in cm³ / g.
[0047] For the aqueous phase heavy metal adsorption test, simulated heavy industrial wastewater containing Pb(II), Cd(II), and Cr(VI) species was used. Pb(II), Cd(II), and Cr(VI) were prepared using standard stock solutions with concentration traceability information, each with an initial mass concentration of 100 mg / L. The pH was adjusted to 5.5 using an acid-base adjusting solution that did not introduce the target metal element, the adsorption temperature was 25℃, and the mass concentration of aerospace-grade zircon powder added was 1.0 g / L. The liquid volume in a single parallel adsorption vessel... The dry mass of the added aerospace-grade zircon powder is 0.200L. The concentration was 0.200 g. The adsorption system was operated under constant temperature water bath shaking conditions at a shaking speed of 150 rpm. Independent parallel adsorption containers were set up at time points of 5 min, 30 min, 60 min, 120 min, 240 min, and 480 min. After reaching the corresponding adsorption time, samples were taken and separated into zircon powder through a 0.22 μm microporous membrane. The residual mass concentrations of Pb(II) and Cd(II) were determined using an inductively coupled plasma mass spectrometry system; the residual concentration of Cr(VI) was determined using a hexavalent chromium-specific colorimetric spectrophotometric detection method. The same colorimetric reagent, reaction time, standard curve, and detection wavelength conditions were used for the same batch of data. No iron-based flocculants were added during the test. For each target species, the time... The adsorption capacity at that time is calculated according to the following formula:
[0048] In the formula: The adsorption contact time is indicated as The instantaneous adsorption capacity of a unit mass of aerospace-grade zircon powder for the corresponding target species, expressed in mg / g; This indicates the initial mass concentration of the corresponding target species, in mg / L; The adsorption contact time is indicated as The mass concentration of the corresponding target species in the aqueous phase, in mg / L; The volume of liquid in a single adsorption system is expressed in liters (L). The dry mass of aerospace-grade zircon powder added to a single adsorption system is expressed in grams. Under the test conditions of Example 3, L / g, the adsorption capacity of each target species is equal to the corresponding initial mass concentration and time. The difference in residual mass concentration, after unit conversion, is expressed as mg / g.
[0049] The adsorption kinetics were fitted using an integral form of a pseudo-second-order kinetic model:
[0050] In the formula: This indicates the adsorption contact time, in minutes. The adsorption contact time is indicated as The instantaneous adsorption capacity of a unit mass of aerospace-grade zircon powder for the corresponding target species, expressed in mg / g; The value represents the equilibrium adsorption capacity obtained from the fitting, in mg / g. This represents the pseudo-second-order adsorption rate constant, expressed in g / (mg·min). The x-axis is... Perform linear regression on the ordinate, and denote the slope of the fitted line as . The intercept is denoted as ,but , The goodness of fit was determined using the coefficient of determination. evaluate.
[0051] To facilitate a better understanding of the present invention by those skilled in the art, the present invention will be further described below with reference to specific embodiments and comparative examples.
[0052] Example 1: 100 kg of natural zircon sand that actually entered the gradient calcination step after screening and dust removal was used as the measurement standard.
[0053] S1. Raw material pretreatment: Natural zircon sand ore from the same source is screened to remove obvious large foreign objects and lumps, and then dust is removed.
[0054] S2. Preparation of the compound halogenating agent: The total amount of the compound halogenating agent added is 2.0% of the mass of the zircon sand raw material, with a total mass of 2.000 kg. The mass ratio of ammonium fluoride to ammonium chloride is 1:1.35. The mass of ammonium fluoride added is approximately 0.851 kg, and the mass of ammonium chloride added is approximately 1.149 kg. After mixing the ammonium fluoride and ammonium chloride with the zircon sand raw material, the mixture is fed into the gradient calcination equipment.
[0055] S3, Gradient Calcination: Establish an inert atmosphere, raise the temperature to 500℃ at a rate of 6℃ / min, and hold for 45min; without removing the material from the furnace, continue raising the temperature to 800℃ and hold for 50min; continue raising the temperature to 1200℃ and hold for 100min. The three stages are completed continuously.
[0056] S4. Cooling: After the third stage at 1200℃ is completed, heating is stopped, and the calcined material is cooled to room temperature with the furnace. Visible agglomerates that affect the subsequent stable supply are deagglomerated to obtain high-temperature purified zircon sand semi-finished product.
[0057] S5. Three-stage electromagnetic separation: The high-temperature purified zircon sand semi-finished product is sent to the 0.8T first-stage electromagnetic separation zone, the obtained main zircon sand stream is collected and sent to the 1.0T second-stage electromagnetic separation zone, and then the obtained main zircon sand stream is collected and sent to the 1.2T third-stage electromagnetic separation zone to obtain magnetically separated zircon sand concentrate.
[0058] S6. Zirconium Contact Grinding: Magnetic-separated zircon sand concentrate is fed into the grinding equipment. The liners and grinding media in direct contact with the material are made of zirconium material, and ferrous materials are not used as the main direct contact grinding material. Grinding parameters are set according to the equipment's historical calibration conditions, with the sieve gradation reaching the target range as the grinding endpoint.
[0059] S7. Particle size control: Sieves are made using 100-mesh, 200-mesh, and 320-mesh sieves. After normalization with the total mass of the three qualified particle sizes as 100%, the 100-200 mesh particle size is 45%, the 200-320 mesh particle size is 35%, and the powder passing through the 320-mesh sieve is 20%, i.e., 45% + 35% + 20% = 100%.
[0060] S8. Performance evaluation: Impurities were evaluated using the same elemental analysis method, sample pretreatment method, statistical items and result statistical caliber as Comparative Example 1. The total impurity content was reduced by more than 85% compared to Comparative Example 1. The same refractoriness evaluation procedure was used for testing, and the refractoriness of the obtained zircon powder reached more than 1850℃.
[0061] Example 2: 100 kg of natural zircon sand after screening and dust removal was used as the measurement standard. S1, Raw material pretreatment: The raw material was treated according to the same screening and dust removal method as in Example 1.
[0062] S2. Preparation of the compound halogenating agent: The total amount of the compound halogenating agent added is 1.5% of the mass of the zircon sand raw material, with a total mass of 1.500 kg. The mass ratio of ammonium fluoride to ammonium chloride is 1:1.20. The mass of ammonium fluoride added is approximately 0.682 kg, and the mass of ammonium chloride added is approximately 0.818 kg. Mix the compound halogenating agent with the zircon sand raw material.
[0063] S3. Gradient calcination: Establish an inert atmosphere, raise the temperature to 500℃ at a rate of 5℃ / min, and hold for 30min; continue raising the temperature to 800℃ and hold for 40min; continue raising the temperature to 1200℃ and hold for 90min. The three stages are carried out continuously without removing the material from the furnace in between.
[0064] S4. Cooling: After the third stage at 1200℃ is completed, stop heating and allow the material to cool to room temperature with the furnace, and deagglomerate any lumps that affect the subsequent stable supply.
[0065] S5. Three-stage electromagnetic separation: The cooled high-temperature purified zircon sand semi-finished product is sequentially passed through three electromagnetic separation levels of 0.8T, 1.0T and 1.2T. The main zircon sand stream obtained from each level enters the next level of electromagnetic separation to obtain magnetically separated zircon sand concentrate.
[0066] S6. Zirconium Contact Grinding: Grinding is carried out using grinding equipment with linings and grinding media made of zirconium materials that are in direct contact with the material. The equipment is operated according to its historical calibration conditions, and the sieve distribution is used as the basis for determining the grinding endpoint.
[0067] S7. Particle size control: After normalizing the three qualified particle sizes, the 100-200 mesh particle size is 50%, the 200-320 mesh particle size is 30%, and the powder passing through the 320 mesh sieve is 20%, that is, 50%+30%+20%=100%.
[0068] Example 3: Based on the process in Example 1, argon bed mass transfer control was introduced in the third stage at 1200℃ to prepare aerospace-grade zircon powder with a mesoporous structure, and the adsorption behavior of the obtained zircon powder for Pb(II), Cd(II), and Cr(VI) species was evaluated. 100 kg of natural zircon sand after sieving and dust removal was used as the feed standard.
[0069] S1. Raw material pretreatment: Screen the natural zircon sand ore, remove visible foreign matter lumps and obvious agglomerates, and remove dust. The actual net weight of the zircon sand after screening and dust removal is 100kg.
[0070] S2. Preparation of the compound halogenating agent: The total amount of the compound halogenating agent added is 2.0% of the mass of the zircon sand raw material, with a total mass of 2.000 kg. The mass ratio of ammonium fluoride to ammonium chloride is 1:1.35, with an ammonium fluoride feed mass of approximately 0.851 kg and an ammonium chloride feed mass of approximately 1.149 kg. The ammonium fluoride, ammonium chloride, and zircon sand raw material are mixed, and the solid mixture is fed into a vertical gradient calcining device with a bottom gas distribution structure.
[0071] S3. Establishing an inert atmosphere: After the equipment is sealed, the residual air inside is removed, and then 99.999% pure argon gas is introduced to replace and establish an inert atmosphere. The argon gas supply system is equipped with a mass flow control device.
[0072] S4, 500℃ first stage calcination: heat up to 500℃ at 6℃ / min and hold for 45min.
[0073] S5, 800℃ Second Stage Calcination: After the first stage at 500℃ is completed, the material is not removed from the furnace. The temperature is increased to 800℃ at a rate of 6℃ / min and held for 50 minutes.
[0074] S6, 1200℃ Third Stage Calcination and Argon Bed Mass Transfer Control: Continue heating to 1200℃ and hold for 100 minutes. During the third stage holding at 1200℃, ensure that argon gas enters from the gas distribution structure at the bottom of the equipment and passes through the material bed.
[0075] In this embodiment, the effective cross-sectional area of the region where the material bed is located The porosity of the material bed under initial loading conditions is calibrated to 0.196 m². The actual volumetric flow rate of argon gas, calibrated to 0.38 and corrected for operating temperature and pressure. Set as m³ / s, according to Calculated m / s. During the third stage of heat preservation at 1200℃ for 100 min, the set value of the linear velocity between the pores of the bed was maintained.
[0076] S7. Cooling and Depolymerization: After the heat preservation is completed, heating is stopped, and the material is cooled to room temperature with the furnace. The cooled material is taken out, and the agglomerates formed during the high-temperature process are mechanically depolymerized to obtain high-temperature purified zircon sand semi-finished product.
[0077] S8. Three-stage electromagnetic separation: The high-temperature purified zircon sand semi-finished product is sent into the 0.8T first-stage electromagnetic separation zone. The main zircon sand stream obtained from the first stage enters the 1.0T second-stage electromagnetic separation zone. The main zircon sand stream obtained from the second stage enters the 1.2T third-stage electromagnetic separation zone to obtain magnetically separated zircon sand concentrate.
[0078] S9. Zirconia Contact Grinding: The inner wall of the grinding equipment is lined with zirconium ceramic plates, and the grinding media are zirconium oxide grinding balls. Iron plates or steel grinding media are not used. Magnetic separated zircon sand concentrate is fed into the grinding equipment and ground according to the historical calibration conditions of the equipment. The grinding endpoint is controlled by the sieving results.
[0079] S10. Particle Size Control: The ground powder was sequentially sieved using 100 mesh, 200 mesh, and 320 mesh sieves. After normalization of the three qualified particle sizes, the 100-200 mesh particle size accounted for 45%, the 200-320 mesh particle size accounted for 35%, and the powder passing through the 320 mesh sieve accounted for 20%, i.e., 45% + 35% + 20% = 100%. S11. Nitrogen Adsorption-Desorption Pore Structure Test: Zircon powder from Example 3 was subjected to a nitrogen adsorption-desorption test. The degassing temperature was 300℃, and the degassing time was 240 min. The adsorption-desorption isotherm was tested under liquid nitrogen temperature conditions.
[0080] The obtained isotherms exhibited characteristics of a type IV isotherm and a type H3 hysteresis loop. The BET specific surface area was 35.8 m² / g, the total pore volume was 0.082 cm³ / g, the average BJH pore size was 6.4 nm, and the mesopore volume fraction was 88.5%. S12. Adsorption Test: A mixed simulated wastewater was prepared using traceable Pb(II), Cd(II), and Cr(VI) standard stock solutions, with an initial mass concentration of 100 mg / L. The pH was adjusted to 5.5 using an acid-base adjusting solution, and the test temperature was 25℃. 0.200 L of simulated wastewater and 0.200 g of dried zircon powder from Example 3 were added to each adsorption container. The zircon powder dosage was 1.0 g / L.
[0081] The adsorption container was placed in a constant temperature water bath shaker at 150 rpm. Independent parallel adsorption containers were set up for 5 min, 30 min, 60 min, 120 min, 240 min, and 480 min. After each time point, the aqueous phase was sampled and filtered through a 0.22 μm microporous membrane. The concentrations of Pb(II) and Cd(II) were determined using inductively coupled plasma mass spectrometry; the concentration of Cr(VI) was determined using a hexavalent chromium-specific colorimetric spectrophotometer. The adsorption capacities obtained were: Pb(II) 49.2 mg / g, Cd(II) 32.5 mg / g, and Cr(VI) 26.1 mg / g at 480 min. The complete time series data are shown in Table 1 below.
[0082] Table 1:
[0083] S13, Pseudo-second-order dynamic fitting: Calculate the data in the table above respectively. ,by x-axis Perform linear regression with the ordinate as the vertical axis.
[0084] Pb(II) fitting yielded mg / g, g / (mg·min), ; Cd(II) fitting yielded mg / g, g / (mg·min), ; Cr(VI) fitting obtained mg / g, g / (mg·min), .
[0085] The coefficients of determination for the pseudo-second-order kinetic fit of the three target species were all higher than 0.997.
[0086] Comparative Example 1: Natural zircon sand from the same batch as in Examples 1 and 2 was used. The natural zircon sand underwent the same sieving pretreatment without the addition of ammonium fluoride and ammonium chloride, and was not subjected to continuous three-stage gradient calcination at 500℃, 800℃, and 1200℃. The zircon sand raw material was directly heated to 1200℃ for a single high-temperature calcination and held at 1200℃ for 100 minutes. After calcination, the material was cooled, and the cooled material was treated using a conventional single-stage magnetic separation method, without the continuous progressive three-stage electromagnetic separation at 0.8T, 1.0T, and 1.2T. After magnetic separation, ordinary grinding was used for powder production, and the use of zirconium-based materials for the lining and grinding media in direct contact with the zircon sand was not limited. The resulting powder was tested using the same impurity analysis method and refractoriness evaluation procedure as in Examples 1 and 2, and the refractoriness was 1720℃. The total mass fraction of impurities in Comparative Example 1 was used as... The total mass fraction of impurities in the examples is used as... The total impurity content reduction rate of both Example 1 and Example 2 reached over 85%.
[0087] Comparative Example 2: Using Example 1 as a baseline, the same batch of natural zircon sand raw material, total amount of compound halogenating agent, mass ratio of ammonium fluoride to ammonium chloride, maximum calcination temperature, three-stage magnetic separation sequence, zirconium contact powdering method, and detection aperture were used as in Example 1. Based on 100 kg of zircon sand raw material, the total mass of compound halogenating agent was 2.000 kg, ammonium fluoride was approximately 0.851 kg, and ammonium chloride was approximately 1.149 kg. The only variable was the elimination of the two independent holding stages at 500℃ for 45 min and 800℃ for 50 min, allowing the material to be continuously heated to 1200℃ and held at 1200℃ for 100 min. After calcination, the material was cooled in the furnace and then sequentially subjected to three-stage electromagnetic separation at 0.8T, 1.0T, and 1.2T, using the same zirconium contact powdering method as in Example 1. The resulting samples were compared under the same elemental analysis and refractoriness evaluation conditions as in Example 1.
[0088] Comparative Example 3: Using Example 1 as a baseline, the natural zircon sand raw material, total amount of compound halogenating agent, mass ratio of ammonium fluoride to ammonium chloride, gradient calcination conditions of 500℃ / 800℃ / 1200℃, furnace cooling, zirconium contact powdering method, and detection method were all consistent with Example 1. The only variable was the magnetic separation method; instead of using the three-stage continuously increasing magnetic field process of 0.8T→1.0T→1.2T, a single-stage magnetic separation was used. The obtained samples were compared under the same elemental analysis and refractoriness evaluation conditions as in Example 1.
[0089] Comparative Example 4: Using Example 1 as a baseline, the natural zircon sand raw material, compound halogenating agent, gradient calcination, furnace cooling, and the three-stage electromagnetic separation conditions (0.8T→1.0T→1.2T) were all consistent with Example 1. The only variable was the main grinding material that directly contacts the magnetically separated zircon sand concentrate during the powdering stage; ordinary iron-based main contact grinding material was used instead of zirconium contact material. The resulting samples were compared under the same elemental analysis conditions as in Example 1, with the comparison focusing on the changes in iron-related impurity statistics before and after powdering.
[0090] Comparative Example 5: Using Example 1 as a baseline, the natural zircon sand raw material, the gradient calcination temperature and time (500℃ / 800℃ / 1200℃), furnace cooling, three-stage electromagnetic separation (0.8T→1.0T→1.2T), zircon contact powdering, and testing conditions were all consistent with Example 1. The only variable was the absence of ammonium fluoride and ammonium chloride. The zircon sand was heated to 500℃ at a rate of 6℃ / min under an inert atmosphere and held for 45 min, then further heated to 800℃ and held for 50 min, and then further heated to 1200℃ and held for 100 min. After gradient calcination, the sample was cooled in the furnace, followed by three-stage electromagnetic separation at 0.8T, 1.0T, and 1.2T, and then zircon contact powdering. The resulting samples were compared under the same elemental analysis and refractoriness evaluation conditions as in Example 1.
[0091] Comparative Example 6: 100 kg of natural zircon sand after screening and dust removal was used as the feed standard. The total amount of the compound halogenating agent added was 3.0% of the zircon sand raw material mass, with a total mass of 3.000 kg. The mass ratio of ammonium fluoride to ammonium chloride was 1:1.50, with 1.200 kg of ammonium fluoride and 1.800 kg of ammonium chloride. After mixing the compound halogenating agent with the zircon sand raw material, an inert atmosphere was established. The temperature was increased to 500℃ at 8℃ / min and held for 60 min, then increased to 800℃ and held for 70 min, and then increased to 1200℃ and held for 120 min. After completing the 1200℃ stage, the furnace was cooled and the agglomerates were deagglomerated. The cooled main stream was sequentially subjected to three-stage electromagnetic separation at 0.8T, 1.0T, and 1.2T, and then powdered using a zirconium contact mill. Particle size control uses 40% 100-200 mesh, 40% 200-320 mesh, and 20% powder passing through a 320 mesh sieve, i.e., 40% + 40% + 20% = 100%.
[0092] Comparative Example 7: Using 100 kg of natural zircon sand after screening and dust removal as the feed standard, the total addition amount of compound halogenating agent was 2.0%, the mass ratio of ammonium fluoride to ammonium chloride was 1:1.35, the mass of ammonium fluoride was approximately 0.851 kg, and the mass of ammonium chloride was approximately 1.149 kg. Under an inert atmosphere, the temperature was increased to 500℃ at 6℃ / min and held for 45 min, then increased to 800℃ and held for 50 min, and then increased to 1200℃ and held for 100 min. After gradient calcination, the material was cooled in the furnace. The main material was sequentially subjected to three-stage electromagnetic separation at 0.8T, 1.0T, and 1.2T, and then pulverized using zirconium contact powder. The particle size control was 50% 100-200 mesh, 40% 200-320 mesh, and 10% powder passing through a 320 mesh sieve, i.e., 50% + 40% + 10% = 100%.
[0093] Comparative Example 8: Using 100 kg of natural zircon sand after screening and dust removal as the feed standard, the total addition amount of the compound halogenating agent was 2.5%, with a total mass of 2.500 kg. The mass ratio of ammonium fluoride to ammonium chloride was 1:1.35, with ammonium fluoride weighing approximately 1.064 kg and ammonium chloride weighing approximately 1.436 kg. An inert atmosphere was established, and the temperature was increased to 500℃ at a rate of 7℃ / min and held for 45 min, then increased to 800℃ and held for 55 min, and then increased to 1200℃ and held for 105 min. After the 1200℃ stage, the furnace was cooled and the agglomerates were deagglomerated. The main stream was sequentially subjected to three-stage electromagnetic separation at 0.8T, 1.0T, and 1.2T, and then zirconium contact powdering was used. Particle size control uses 45% 100-200 mesh, 40% 200-320 mesh, and 15% powder passing through a 320 mesh sieve, i.e., 45% + 40% + 15% = 100%.
[0094] Quantitative data from Examples 1, 2 and Comparative Example 1 were used to demonstrate that a complete basic purification process chain can achieve a combined result of reduced total impurity content and increased refractoriness.
[0095] The pore structure and aqueous phase adsorption data of Example 3 are used to support further technical branches for argon bed mass transfer control and adsorption applications.
[0096] In industrial production, after each batch of zircon sand is screened and dusted, the actual net feed weight is weighed. The total amount of compound halogenating agent is calculated based on the net feed weight, and the two halogenating agents are measured separately. When the production scale changes, the feed weight is increased or decreased proportionally.
[0097] For equipment implementing mesoporous branching, the actual volumetric flow rate of argon gas is calculated based on the actual effective cross-sectional area of the bed and the packing porosity during the third stage at 1200℃. This ensures that the linear velocity between the bed pores reaches the corresponding set value. When scaling up the equipment, it is not sufficient to simply keep the total argon flow rate constant; rather, it should be based on… Calculate the actual volumetric flow rate of argon gas for the corresponding equipment. Adjust the operating conditions of the grinding equipment according to the target particle size distribution. The specific grinding operating parameters are determined based on the historical calibration relationship of the grinding equipment, and the endpoint is confirmed through sieving results.
[0098] Zircon powder prepared using a basic purification process can be used as a refractory powder for precision casting cores in aerospace applications. Its application can be tailored to specific core systems and corresponding binder systems. Mesoporous zircon powder prepared using the process in Example 3 can serve as a solid adsorbent carrier in aqueous systems containing Pb(II), Cd(II), and Cr(VI) species. For actual industrial wastewater, the adsorbent dosage and contact time are determined according to the specific influent composition. The entire process material chain is sequentially linked. Natural zircon sand ore, after pretreatment, is mixed with a compound halogenating agent and then subjected to gradient calcination. After cooling and deagglomeration, the calcined material sequentially enters a three-stage electromagnetic separation process. The magnetically separated concentrate enters a zirconium contact powdering process, and the ground powder is sieved and classified to obtain aerospace-grade zircon powder with a closed-cell particle size distribution.
[0099] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.
[0100] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. It should be noted that any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A gradient calcination, halogenation, and multi-stage magnetic separation purification process for aerospace-grade zircon powder, characterized by: Includes the following steps: S1. Raw material pretreatment: The natural zircon sand ore is screened and dusted to remove large foreign objects, lumps and free dust to obtain zircon sand raw material; S2. Compound halogenation gradient calcination: Zircon sand raw material is mixed with a compound halogenating agent composed of ammonium fluoride and ammonium chloride. The mass ratio of ammonium fluoride to ammonium chloride is 1:1.20-1.35, and the total amount of compound halogenating agent added is 1.5%-2.0% of the mass of zircon sand raw material. The mixed material is placed under an inert atmosphere, and the same batch of material is subjected to a first stage calcination at 500℃, a second stage calcination at 800℃, and a third stage calcination at 1200℃ without leaving the furnace. The holding time for the first stage calcination at 500℃ is 30-45 min, the holding time for the second stage calcination at 800℃ is 40-50 min, and the holding time for the third stage calcination at 1200℃ is 90-100 min. The heating rate between each stage is 5-6℃ / min. S3. Cooling treatment: After the third stage of calcination at 1200℃ is completed, heating is stopped, and the calcined material is cooled to room temperature with the furnace. Agglomerates that affect the subsequent stable supply are deagglomerated to obtain high-temperature purified zircon sand semi-finished product. S4. Progressive three-stage electromagnetic separation: The main stream of high-temperature purified zircon sand semi-finished product first passes through the first stage electromagnetic separation with a magnetic field strength of 0.8T. The main zircon sand stream obtained from the first stage electromagnetic separation is then sent to the second stage electromagnetic separation with a magnetic field strength of 1.0T. Finally, the main zircon sand stream obtained from the second stage electromagnetic separation is sent to the third stage electromagnetic separation with a magnetic field strength of 1.2T to obtain magnetically separated zircon sand concentrate. S5. Zirconium Contact Grinding: After the third-stage electromagnetic separation is completed, the magnetically separated zircon sand concentrate is ground. The grinding equipment liner and grinding media that are in direct contact with the magnetically separated zircon sand concentrate are made of zirconium material. The zirconium material is a zirconium-containing non-ferrous material that forms the direct contact surface, and ferrous materials are not used as the main grinding material in direct contact with the magnetically separated zircon sand concentrate. S6. Particle size control: The powder obtained from grinding is sieved and classified to obtain aerospace-grade zircon powder.
2. The gradient calcination, halogenation, and multi-stage magnetic separation purification process for aerospace-grade zircon powder according to claim 1, characterized in that: The total amount of compound halogenating agent and the mass ratio of ammonium fluoride to ammonium chloride are selected from one of the following combinations: the total amount of compound halogenating agent is 1.5% of the mass of zircon sand raw material, and the mass ratio of ammonium fluoride to ammonium chloride is 1:1.20; or the total amount of compound halogenating agent is 2.0% of the mass of zircon sand raw material, and the mass ratio of ammonium fluoride to ammonium chloride is 1:1.
35.
3. The gradient calcination halogenation purification and multi-stage magnetic separation process for aerospace-grade zircon powder according to claim 1 or 2, characterized in that: The gradient calcination parameters are selected from one of the following combinations: the heating rate between each stage is 5℃ / min, the first stage calcination is held at 500℃ for 30min, the second stage calcination is held at 800℃ for 40min, and the third stage calcination is held at 1200℃ for 90min; or the heating rate between each stage is 6℃ / min, the first stage calcination is held at 500℃ for 45min, the second stage calcination is held at 800℃ for 50min, and the third stage calcination is held at 1200℃ for 100min.
4. The gradient calcination, halogenation, and multi-stage magnetic separation purification process for aerospace-grade zircon powder according to claim 3, characterized in that: The total amount of compound halogenating agent added is 2.0% of the mass of zircon sand raw material. The mass ratio of ammonium fluoride to ammonium chloride is 1:1.
35. The heating rate between each stage is 6℃ / min. The first stage calcination is held at 500℃ for 45min, the second stage calcination is held at 800℃ for 50min, and the third stage calcination is held at 1200℃ for 100min.
5. The gradient calcination, halogenation, and multi-stage magnetic separation purification process for aerospace-grade zircon powder according to claim 3, characterized in that: The total amount of compound halogenating agent added is 1.5% of the mass of zircon sand raw material, the mass ratio of ammonium fluoride to ammonium chloride is 1:1.20, the heating rate between each stage is 5℃ / min, the first stage calcination is held at 500℃ for 30min, the second stage calcination is held at 800℃ for 40min, and the third stage calcination is held at 1200℃ for 90min.
6. The gradient calcination, halogenation, and multi-stage magnetic separation purification process for aerospace-grade zircon powder according to claim 1, characterized in that: The first, second, and third stages of electromagnetic separation are carried out continuously in the order of increasing magnetic field strength (0.8T, 1.0T, and 1.2T). The main zircon sand stream obtained from the first stage of electromagnetic separation is used as the feed for the second stage of electromagnetic separation, and the main zircon sand stream obtained from the second stage of electromagnetic separation is used as the feed for the third stage of electromagnetic separation.
7. The gradient calcination halogenation purification and multi-stage magnetic separation process for aerospace-grade zircon powder according to claim 1 or 6, characterized in that: Zirconium contact grinding is located after the three-stage electromagnetic separation. In the grinding equipment, the liner and grinding media that are in direct and continuous contact with the magnetically separated zirconium sand concentrate are both made of zirconium material to form the direct contact surface.
8. The gradient calcination, halogenation, and multi-stage magnetic separation purification process for aerospace-grade zircon powder according to claim 1, characterized in that: The particle size distribution formed in step S6, based on the total mass of three qualified particle grades—100-200 mesh, 200-320 mesh, and powder passing through a 320 mesh sieve—is as follows: 40%-50% of the 100-200 mesh particle grade passing through a 100 mesh sieve and retained by a 200 mesh sieve; 30%-40% of the 200-320 mesh particle grade passing through a 200 mesh sieve and retained by a 320 mesh sieve; and 10%-20% of the powder passing through a 320 mesh sieve; and the sum of the mass percentages of the three qualified particle grades is 100%.
9. The gradient calcination, halogenation, and multi-stage magnetic separation purification process for aerospace-grade zircon powder according to claim 8, characterized in that: 45% of the particles are 100-200 mesh, 35% are 200-320 mesh, and 20% pass through a 320 mesh sieve.
10. The gradient calcination, halogenation, and multi-stage magnetic separation purification process for aerospace-grade zircon powder according to claim 8, characterized in that: 50% of the particles are 100-200 mesh, 30% are 200-320 mesh, and 20% are powder that passes through a 320 mesh sieve.